Interlaminar fracture micro-mechanisms in toughened carbon fibre reinforced plastics investigated via synchrotron radiation computed tomography and laminography. (April 2015) - Borstnar, G.; Mavrogordato, M.N.; Helfen, L.; Sinclair, I.; Spearing, S.M.
Abstract: Synchrotron Radiation Computed Tomography (SRCT) and Synchrotron Radiation Computed Laminography (SRCL) permit 3D non-destructive evaluation of fracture micro-mechanisms at high spatial resolutions. Two types of particle-toughened Carbon Fibre Reinforced Polymer (CFRP) composites were loaded to allow crack growth in Modes I and II to be isolated and observed in standard and non-standard specimen geometries. Both materials failed in complex and distinct failure modes, showing that interlaminar fracture in these materials involves a process zone rather than a singular crack tip. The work indicates that incorporating particle/resin, fibre/interlayer and neat resin failure is essential within models for material response, since the competition between these mechanisms to provide the energetically favourable crack path influences the macro-scale toughness. The work uniquely combines the strengths of SRCT and SRCL to compare failure micro-mechanisms between two specimen geometries, whilst assessing any edge effects and providing powerful insight into the complex micro-mechanical behaviour of these materials.